Upaya Pengasuh Dalam Stimulasi Perkembangan Bahasa Pada Anak Usia Balita Melalui Kegiatan Pembiasaan Sehari-hari di Daycare Taman Isola UPI - Fauziah, Fitri Nurul; Achdiani, Yani; Rinekasari, Nenden Rani (FamilyEdu: Jurnal Pendidikan Kesejahteraan Keluarga, 2019)
Some children have difficulty in accepting the language so that the child slowly reveal more use language such as body language in expressing his desire. The problem of this research is how the baby sistter efforts in the stimulation of language development kindergarten through habituation daily activities at Daycare Taman Isola UPI. The purpose of this study was to obtain an overview of the efforts baby sistters in the stimulation of language development kindergarten through habituation daily activities at Daycare focusing routine, spontaneous and exemplary. This research using descriptive method, as a means of collecting data in the form of a questionnaire distributed to respondents, the baby sistter at Daycare Taman Isola UPI as many as 14 people. The findings of research on baby sistter efforts in the stimulation of language development kindergarten through habituation everyday activities that most  the baby sistters are already making efforts to give an example, invites, familiarize and train through habituation in daycare. Recommendation results of this study aimed to baby sistters in order to deliver rewards in the form of praise when the child is able to perform the achievements of the language development appropriate to his age, he is also concerned about the development of children's language training to develop the skills and knowledge of baby sistter.